Telemedicine during the Coronavirus Disease (COVID-19) Pandemic: A Multiple Sclerosis (MS) Outpatients Service Perspective - Francesco Corea; Silvia Ciotti; Antonella Cometa; Claudia De Carlo; Giancarlo Martini; Silvano Baratta; Mauro Zampolini (MDPI AG, 2021)
Background: During the COVID-19 pandemic, the need for a broader implementation of telemedicine for many diseases has become apparent. Televisits are one type of telemedicine in which clinical visits are conducted remotely using an audio-visual connection with the patient at home. The use of televisits is more established in Stroke care but was also recently formally evaluated for Multiple Sclerosis (MS). This retrospective case series describes patient characteristics and reasons for televisits in persons with MS during the COVID-19 pandemic outbreak in Italy, which was declared in February 2020. Methods: Recruitment occurred in a general hospital based MS clinic during Italy's lockdown months period (9 March-18 May). Each subject completed at least one televisit. The baseline data included were demographics and MS history; reasons for the remote house calls were analyzed focusing on COVID-19 related needs. Results: Forty-six participants completed at least one study visit. The patients enrolled were more often females suffering from Relapsing Remitting Multiple Sclerosis (RRMS). Half of the patients had an intermediate level of education and lived within a 60 min drive from the clinic. These patients predominately had a short disease duration and were mostly involved in oral treatment. The main reasons for the call were drug use and counseling on social distancing. In 5 cases, COVID-19 infection was reported. Conclusions: Televisits during the COVID-19 outbreak demonstrated their utility as a care delivery method for MS. Hence, it is vital to facilitate the implementation of this technology in common practice to both face infectious threats and increase accessibility of the health care system.